2021
DOI: 10.3390/molecules26061697
|View full text |Cite
|
Sign up to set email alerts
|

S-allyl Cysteine Enhances Testosterone Production in Mice and Mouse Testis-Derived I-10 Cells

Abstract: Hypogonadism, associated with low levels of testosterone synthesis, has been implicated in several diseases. Recently, the quest for natural alternatives to prevent and treat hypogonadism has gained increasing research interest. To this end, the present study explored the effect of S-allyl cysteine (SAC), a characteristic organosulfur compound in aged-garlic extract, on testosterone production. SAC was administered at 50 mg/kg body weight intraperitoneally into 7-week-old BALB/c male mice in a single-dose expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
(27 reference statements)
2
1
0
1
Order By: Relevance
“…Based in our understanding in the field, the main contribution of these findings consists in demonstrating that chronic and moderate CR during aging prolongs the reproductive function in aged rats. This fact is support by several studies that have demonstrated the existence of a direct correlation between T concentrations and MSB such that a deficit of T affects MSB even in young adult animals [ 30 , 32 , 44 , 45 ]. However, correct performance of MSB requires the synergic activity of T and E 2 because an increase continued may generate feminization of the brain and increase latencies during MSB tests [ 46 ].…”
Section: Discussionsupporting
confidence: 74%
“…Based in our understanding in the field, the main contribution of these findings consists in demonstrating that chronic and moderate CR during aging prolongs the reproductive function in aged rats. This fact is support by several studies that have demonstrated the existence of a direct correlation between T concentrations and MSB such that a deficit of T affects MSB even in young adult animals [ 30 , 32 , 44 , 45 ]. However, correct performance of MSB requires the synergic activity of T and E 2 because an increase continued may generate feminization of the brain and increase latencies during MSB tests [ 46 ].…”
Section: Discussionsupporting
confidence: 74%
“…Based in our understanding in the field, the main contribution of these findings consists in demonstrating that chronic and moderate CR during aging prolongs the reproductive function in aged rats. This fact is support by several studies that have demonstrated the existence of a direct correlation between T concentrations and MSB such that a deficit of T affects MSB even in young adult animals [30,32,44,45]. However, correct performance of MSB requires the synergic activity of T and E2 because an increase continued may generate feminization of the brain and increase latencies during MSB tests [46].…”
Section: Discussionsupporting
confidence: 58%
“…Diversos trabajos han demostrado la existencia de una correlación directa entre las concentraciones de T y la CSM, cuando hay un déficit de T la CSM se ve afectada, incluso cuando los animales son adultos jóvenes (Chen et al, 2005;Govic et al, 2008;Rana et al, 2021). Sin embargo, es necesaria la actividad sinérgica de la T y del E2 para el correcto despliegue de la CSM, pues un aumento de E2 resulta en una posible feminización del cerebro y aumenta las latencias en las pruebas de CSM .…”
Section: Página 56unclassified
“…The difference in our results may be explained by the use of different administration doses along with different terms of exposure to garlic and different factors involved in the pathogenesis of the disease [ 97 , 98 ]. Moreover, Rana et al [ 99 ] also showed that “a key organosulfur compound in aged-garlic extract, S-allyl cysteine (SAC), enhances the testosterone level through activating the PKA pathway and can be a probable target for hypogonadism therapeutics” [ 99 ]. Garlic contains high amounts of zinc and selenium, and these substances along with diallyl sulfide have a regulatory role in testicular activities, especially the production of steroidogenic enzymes [ 100 ].…”
Section: Discussionmentioning
confidence: 99%